Hamlet - Shakespeare, William, 1564-1616 (Staged collection., 2024)
"When Hamlet, Prince of Denmark, hears rumors of his late father's ghost being sighted around the castle, he seeks out the impossible. Upon finding the apparition of the late King, he receives a shocking revelation: his father was murdered. If that terrible betrayal wasn't enough, the King claims that his murderer is none other than Hamlet's own uncle Claudius; his mother's new husband and new King of Denmark. Furious, Hamlet swears to avenge his father, and devises a plot to feign madness in order to reveal the truth and enact his revenge. But Claudius has his own plans, and soon a chain of events is set in motion that brings devastation to the entire court"--Amazon.com.